1996
DOI: 10.1021/bc950069+
|View full text |Cite
|
Sign up to set email alerts
|

Labeling a Hydrazino Nicotinamide-Modified Cyclic IIb/IIIa Receptor Antagonist with 99mTc Using Aminocarboxylates as Coligands

Abstract: A series of 99mTc complexes containing a hydrazinonicotinamide-conjugated cyclic IIb/IIIa receptor antagonist, cyclo(D-Val-NMeArg-Gly-Asp-Mamb-(hydrazinonicotinyl-5- (6-aminocaproic acid))), were synthesized in high yield using tricine or other aminocarboxylates as coligands. These 99mTc complexes have the potential to be used as thrombus imaging agents. The radiolabeling of the HYNIC-conjugated cyclic IIb/IIIa peptide (HYNICtide) was carried out by reaction with pertechnetate in the presence of excess tricine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
2
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 26 publications
10
113
2
7
Order By: Relevance
“…First, to preserve the convenience of HYNIC radiochemistry we adopted a phosphine compound as a third coligand, as described by Edwards et al (17,18). To this end, although tricine alone has been widely used as a coligand for HYNIC radiochemistry, in which 2 tricine molecules form a well-defined coordination complex with 99m Tc and the hydrazine group of HYNIC, the tricine chelation core is known to be less stable under dilute conditions (17)(18)(19)(20)(21)(22). By including TPPTS in the coordination chemistry, 99m Tc-duramycin remains stable both in solution and in vivo, consistent with the prior findings (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…First, to preserve the convenience of HYNIC radiochemistry we adopted a phosphine compound as a third coligand, as described by Edwards et al (17,18). To this end, although tricine alone has been widely used as a coligand for HYNIC radiochemistry, in which 2 tricine molecules form a well-defined coordination complex with 99m Tc and the hydrazine group of HYNIC, the tricine chelation core is known to be less stable under dilute conditions (17)(18)(19)(20)(21)(22). By including TPPTS in the coordination chemistry, 99m Tc-duramycin remains stable both in solution and in vivo, consistent with the prior findings (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…In this latter respect, the chemistry of technetium with 2-hydrazino-nicotinamide derivatized peptides has received considerable attention [4][5][6]. In modeling the chemistry of the Tc-organohydrazino core of these radiopharmaceuticals, we have developed the chemistry of a class of compounds derived from the rhenium bispyridinodiazene core, {Re(η 2 -HNNC 5 H 4 N)(η 1 -NNC 5 H 4 NH)} 3+ , shown schematically [7] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…It was assumed that the 99m Tc species is coordinated by two tricine molecules and the terminal N-atom of the hydrazine group of HYNIC in the resulting Tc-HYNIC-protein complex [41]. Detailed HPLC analysis indicated that the complex can reversibly adopt various forms, depending on temperature, reaction time and pH.…”
Section: Chelators For 99m Tc Labeling Of Somatostatin Analogsmentioning
confidence: 99%